2004
DOI: 10.1001/archpedi.158.8.786
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Treatment for Child and Adolescent Traumatic Stress

Abstract: Child and adolescent posttraumatic stress disorder treatment research lags behind both adult posttraumatic stress disorder treatment research and other child treatment research. There is considerable need to establish a programmatic approach to developing evidence-based child trauma treatment. Barriers to conducting child trauma treatment research include sensitivity to the rights of victims and child service models that perceive research as intruding on vulnerable children at critically sensitive points in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 19 publications
0
27
0
3
Order By: Relevance
“…Difficulties in establishing an evidence-based child trauma treatment encompass the sensitivity to the rights of victims as well as child service models that consider research as intrusive at critically sensitive points in the development of vulnerable children [17].…”
Section: Psychopharmacotherapy Of Ptsd Among Children and Adolescentsmentioning
confidence: 99%
“…Difficulties in establishing an evidence-based child trauma treatment encompass the sensitivity to the rights of victims as well as child service models that consider research as intrusive at critically sensitive points in the development of vulnerable children [17].…”
Section: Psychopharmacotherapy Of Ptsd Among Children and Adolescentsmentioning
confidence: 99%
“…Even though a number of systematic reviews focusing on intervention for children and adolescents who have experienced trauma have been conducted (e.g., Adler-Nevo & Manassis, 2005;Cohen, Mannarino, Murray, & Igelman, 2006;Feeny, Treadwell, Foa, & March, 2004;Lawrence, De Silva, & Henley, 2010;Persson & Rousseau, 2009;Pine & Cohen, 2002;Silverman et al, 2008;Taylor & Chemtob, 2004), reviews focusing specifically on school-based intervention are virtually nonexistent. The aim of our study was therefore to identify and examine the effectiveness of school-based intervention programs for reducing posttraumatic stress disorder (PTSD) symptoms.…”
mentioning
confidence: 99%
“…13 The only randomized study on refugees in highincome settings has shown smaller positive gains for a group of adolescents engaged in drama therapy. 14 Cohen and coworkers 15 and Taylor and Chemtob 16 have reviewed the limited number of studies on interventions for trauma-exposed children and adolescents in high-income settings. These 2 review articles show empirical support for cognitive behavioral treatments (CBTs), with a larger evidence base for abused children.…”
mentioning
confidence: 99%